High temperature coke characteristics in the blast furnace : evaluation of coke properties in the raceway area - Lundgren, Maria; Ökvist, Lena Sundqvist; Hyllander, Gunilla; Jansson, Björn; Björkman, Bo (Luleå tekniska universitet, Industriell miljö- och processteknik, 2012)
Core-drilling into the coke bed of raceway and hearth has been performed in the LKAB Experimental Blast Furnace (EBF®) during short stoppages aiming to characterize raceway conditions corresponding to different operational conditions. All coke operation, injection of pulverized coal and injection of a mixture of coal and blast furnace flue dust (BFD) were evaluated and compared. The samples have been studied regarding particle size and distribution, coke have been evaluated with chemical composition and thermal history, i.e. coke graphitization degree. In addition, the results have been compared to drilled raceway core samples from SSAB industrial blast furnace in Luleå. Coke in drill-cores consists of bosh, raceway and deadman coke. In comparison with charged coke this coke has changed characteristics depending on the exposed conditions which vary along the radius of each drilled core. Coke in raceway area has increased ash content due to gasification of C and the ash composition is altered due to both reduction and gasification of ash minerals as e.g. SiO2 and alkalis in raceway and oxidation/condensation of gaseous compounds and uptake of compounds from the melt. Coke exposed to highest temperatures in the raceway area have increased the most in graphitization degree, and subsequent bird’s nest and deadman cokes graphitization degrees decreases. K2O-content in coke correlates to the graphitization degree as well as the SiO2/Al2O3 quotient which decreases at higher temperatures. Presence of slag and coke aggregates indicates the formation of bird’s nests at the end of the raceway. The end of raceway and position of a significant bird's nest in the industrial samples are indicated by the increasing content of K2O and increasing ratio of SiO2/Al2O3 in coke. In the industrial BF the pronounced formation of a bird’s nest redirect the gas from moving towards the BF center. As a result the coke in deadman cannot be heated and the temperature indicated by the graphitization degree decreases.Injection of BFD ...